2022
DOI: 10.1097/ta.0000000000003646
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine reduces organ injury and improves motor function after traumatic brain injury in mice

Abstract: Fluoxetine reduces organ injury in a mouse model of traumatic brain injury

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Clustering analysis showed that molecules involved in inflammatory responses, metabolic disorders, tissue repair, and bacterial defense were significantly dysregulated. These findings suggested similarities in physiopathological processes between the intestines and other organs in response to traumatic injury [ 27 , 28 ]. The landscape of protein reprogramming can reveal the molecular mechanisms of TCI progression and provide data support for subsequent research.…”
Section: Discussionmentioning
confidence: 99%
“…Clustering analysis showed that molecules involved in inflammatory responses, metabolic disorders, tissue repair, and bacterial defense were significantly dysregulated. These findings suggested similarities in physiopathological processes between the intestines and other organs in response to traumatic injury [ 27 , 28 ]. The landscape of protein reprogramming can reveal the molecular mechanisms of TCI progression and provide data support for subsequent research.…”
Section: Discussionmentioning
confidence: 99%
“…cognitive impairment was demonstrated to be mediated by 5-HT in the hippocampus in a tryptophan depletion clinical trial [112]. Considering such evidence, the role of serotonin in treating or altering the outcomes of TBI is under study [66,116,117]. Data about the efficacy of selective serotonin reuptake inhibitors (SSRIs) in treating TBI patients comes from preclinical models.…”
Section: Serotoninmentioning
confidence: 99%
“…Created with www. Biore nder placebo [117]. Craine et al studied the role of chronic IP milnacipran treatment (30 mg/kg/day), a serotonin-norepinephrine reuptake inhibitor (SNRI), in improving cognition in male rats subjected to frontal lobe injury.…”
Section: Serotoninmentioning
confidence: 99%
“…A pilot study suggested that the diversity of the microbial ecosystem in brain tumour patients was less than the healthy controls [ 14 ], while caecal content transfer experiments in mice revealed that cancer-associated alteration in caecal metabolites was involved in late-stage glioma progression [ 15 ]. In addition, there is clear evidence that TBI can cause gut microbiota dysbiosis [ 16 ], while disruption of the gut barrier and depletion of the gut microbiota are associated with neurologic outcomes following TBI [ 17 ]. With a growing understanding of BGA, people have a strong interest in studying the influences of BGA in neural recovery and neurorehabilitation after TBI.…”
Section: Introductionmentioning
confidence: 99%